2022
DOI: 10.3390/d14110961
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Giant Triton (Charonia tritonis), from Exploitation to Coral Reef Protector?

Abstract: Charonia tritonis (Charoniidae), one of the largest marine gastropods and an echinoderm specialist, preys on Crown-of-Thorns starfish (CoTS), a recurring pest that continues to be a leading cause of coral mortality on Indo-Pacific reefs. Widespread historical exploitation has impacted their numbers, with standing populations considered rare throughout their habitat. Their life-stage attributes, i.e., teleplanic larvae, planktotrophic phase spanning years permitting transoceanic dispersal, and recruitment to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 261 publications
0
3
0
Order By: Relevance
“…Species identification was based on features such as smooth, broad, and flattened spiral ribs with wavy, puckered edges, and a broad, short siphonal canal with thin folds along the columellar wall (Motti et al. 2022 ). The specimens have been deposited at the Specimen Museum of the School of Marine Biology and Fisheries at Hainan University ( http://en.hainanu.edu.cn/ , Xiang, Xiangzhang@hainanu.edu.cn ), with voucher numbers ctri20181201 and ctri20181202.…”
Section: Methodsmentioning
confidence: 99%
“…Species identification was based on features such as smooth, broad, and flattened spiral ribs with wavy, puckered edges, and a broad, short siphonal canal with thin folds along the columellar wall (Motti et al. 2022 ). The specimens have been deposited at the Specimen Museum of the School of Marine Biology and Fisheries at Hainan University ( http://en.hainanu.edu.cn/ , Xiang, Xiangzhang@hainanu.edu.cn ), with voucher numbers ctri20181201 and ctri20181202.…”
Section: Methodsmentioning
confidence: 99%
“…Triton trumpet conches are widespread in tropical, subtropical and Mediterranean waters, including the Mediterranean and Adriatic Seas (Motti et al 2022). The colour of the Keszthely specimen (Fig.…”
Section: Description Of the Objectmentioning
confidence: 99%
“…These claims followed the first documented outbreak on the Great Barrier Reef (GBR) in Australia, coinciding with exhaustive fishing-induced depletion of the giant triton, Charonia tritonis, a predator of adult CoTS (Endean 1973). However, the effectiveness of predation by C. tritonis on CoTS remains unresolved (Ormond et al 1990;Motti et al 2022), given that reported consumption rates are low, < 1 wk −1 (Endean 1969;Birkeland 1989b), and their historical (cf. pre-harvest) densities are unknown (Hall et al 2017).…”
Section: Introductionmentioning
confidence: 99%